Peduli Kesehatan Jiwa Lansia Melalui Latihan “Asitifrop” (Affirmasi Positif dan Relaksasi Otot Progresif) Dan Eteksidini Kesehatan Mental Lansia Di Desa Jemundo - Aristina Halawa; Ethica Sari; NadyaAmbarwati; Ni Putu Widari (Universitas Sahid Surakarta, 2025)
According to the World Health Organization (WHO), the global prevalence of mental disorders in the elderly is 61.6%. 2018 Balitbangkes data shows that there are 4 major health problems experienced by the elderly, namely hypertension, diabetes mellitus (DM), stroke and emotional mental disorders. Mental health disorders that often occur in the elderly are depression, anxiety and dementia. The aim of this community service is to increase the elderly's knowledge about mental health, prevent mental health problems by carrying out positive affirmations and progressive muscle relaxation and cadres can carry out early detection of mental health problems in the elderly. The methods used in this community service are counseling about mental health for the elderly,